2010
DOI: 10.1007/s12161-010-9146-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hen Lysozyme on Proteic Profiles of Grana Padano Cheese through SELDI-TOF MS High-Throughput Technology during the Ripening Process

Abstract: Lysozyme is used in cheese manufacture in order to prevent blowing in cheeses caused by Clostridium tyrobutyricum. Being an egg derivative, the presence of lysozyme must be included on the label for residual allergenic risk (2003/89/CE). The aim of this study was to evaluate the presence of lysozyme on proteic profiles of typical Italian cheeses such as Grana Padano through surface-enhanced laser desorption/ionization time-of-flight mass spectrometry. The proteolytic activity of ripening (from 0 to 24 months),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Therefore, lysozyme contained in jenny milk was found to be an important inhibitor agent against coliform bacteria, although its addition to ewe milk did not affect the number of Clostridium butyricum spores Cosentino et al 2013b). The lower content of coliforms in treated ewe cheese was in agreement with results from the literature on reduced growth of C. butyricum in Grana Padano (Iaconelli et al 2008;Dragoni et al 2011) and Gouda cheese (Bester and Lombard 1990). Martìnez-Cuesta et al (2010) observed a higher contamination of Clostridium in Manchego control cheese compared with that treated with lysozyme HEW.…”
Section: Jenny Milk As Inhibitor In Cheese Makingsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, lysozyme contained in jenny milk was found to be an important inhibitor agent against coliform bacteria, although its addition to ewe milk did not affect the number of Clostridium butyricum spores Cosentino et al 2013b). The lower content of coliforms in treated ewe cheese was in agreement with results from the literature on reduced growth of C. butyricum in Grana Padano (Iaconelli et al 2008;Dragoni et al 2011) and Gouda cheese (Bester and Lombard 1990). Martìnez-Cuesta et al (2010) observed a higher contamination of Clostridium in Manchego control cheese compared with that treated with lysozyme HEW.…”
Section: Jenny Milk As Inhibitor In Cheese Makingsupporting
confidence: 91%
“…95/2/EC (quantum satis in ripened cheese) (Pellegrino and Tirelli 2000;Scharfen et al 2007;Schneider et al 2011). In Italy, the use of lysozyme is quite widespread: this enzyme has been employed in the process of making several cheeses, such as Grana Padano cheese, grated hard cheese mixtures (Iaconelli et al 2008;Panari and Filippi 2009) and semihard goat and ewe cheeses (Dragoni et al 2011;Schneider et al 2011). The content of lysozyme from egg in cheese ranges from 50 to 350 μg/g of cheese, with the maximum of 400 μg/g of cheese depending on the type of cheese and the production process (Pellegrino and Tirelli 2000;Á vila et al 2014).…”
Section: Jenny Milk As Inhibitor In Cheese Makingmentioning
confidence: 99%
“…Concern about the allergenicity of enzymes such as lysozyme is also an issue since a low but significant percentage of the population is predisposed to egg allergies (Ouahidi et al 2011). Nonetheless within the food and beverage industry lysozyme is employed as a preservative, and there are mixed views about its allergenicity potential at levels used in cheese (Dragoni et al 2011) and wine (Weber et al 2009). Since lysozyme is covalently attached to cellulose in the paradigm of this study it is probable that it would undergo minimal duration of contact with the skin in a hygienic or antimicrobial wipe product.…”
Section: Resultsmentioning
confidence: 99%
“…Lysozyme was found to remain unaltered during ripening (up to 24 months) of a hard-type cheese by using SELDI-TOF/MS (Dragoni et al, 2011). Another method which combines immunocapture purification and MALDI-TOF-MS analysis was also developed for the detection of lysozyme in cheese samples (Schneider Nadine et al, 2010), with a LOD of 5 mg/kg lysozyme in cheese.…”
Section: Detection Of Lysozyme In Dairy Productsmentioning
confidence: 99%